Transformative Frames for Climate Threat in the Anthropocene - Hurlbert, Margot (Frontiers in Sociology, 2021)
This is a mini review of literature surrounding new frames of the threat of climate change including ‘Anthropocene,’ ‘climate crisis,’ ‘climate emergency,’ and ‘climate catastrophe.’ The specific meanings and consequences of these frames are discussed and an argument why these frames are needed and risk is not enough. Ultimately, this article concludes these new framings assist transformative change by opening up climate change science, citizen engagement, and policy response. However, no one frame and no one associated policy is supported, but a plurality, dependent on context, and culture.